This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
To solve this problem, we consider the two cases for absolute value. If x − 1 < 0 , we can replace ∣ x − 1 ∣ with − ( x − 1 ) . We can see that as x approaches 1 from the left, x - 1 approaches 0 from the left. Therefore,
x → 1 − lim x − 1 ∣ x − 1 ∣ = x → 1 − lim x − 1 − ( x − 1 ) = − 1
Similarly, for the case where x − 1 > 0 , we have ∣ x − 1 ∣ = x − 1 .
x → 1 + lim x − 1 ∣ x − 1 ∣ = x → 1 + lim x − 1 x − 1 = 1
Since the left hand limit does not equal the right hand limit, the limit does not exist.